Scleral buckle is good option for treatment of uncomplicated retinal detachment - Takasaka,Iuuki (2012)
OBJETIVE: To describe the reattachment rate and visual acuity results of patients with uncomplicated rhegmatogenous retinal detachment who underwent segmental scleral buckle surgery. METHODS: Prospective case series of 100 patients with visual loss or symptoms (floaters and photopsia) of less than 30 days' duration scheduled for surgery. No patient had a retinal break greater than 30°, a retinal detachment larger than 2 quadrants or proliferative vitreoretinopathy. RESULTS: The 1-week, 1-month, and 6-month anatomical success rates were 93%, 100%, and 100%, respectively. Seven patients underwent one additional retinal detachment surgery (pars plan vitrectomy) after primary failure at 1-week follow-up. The preoperative, 1-month, and 6-month best correct visual acuity were 20/100, 20/80, and 20/50, respectively. The postoperative complications were: eyelid edema in 10% of the patients, transient ocular hypertension in 5%, macular pucker in 3%, transient diplopia in 3%, and hyphema (<0.5mm) in 1%. CONCLUSION: In patients with uncomplicated retinal detachment, segmental scleral buckle showed a very good anatomical and functional success, with a few number of major complications.